Pro Mapping in BizTalk Server 2009 - Dawson, Jim; Wainwright, John (Apress : Imprint: Apress, 2009)
Learning good map design techniques for BizTalk Server will make a huge difference to the processing speed of your implementation, as well as to the scalability and maintainability of your code. Regardless of your experience, expert authors Jim Dawson and John Wainwright ensure you make the right choices to reap the rewards and avoid the potential penalties of poor design. Pro Mapping in BizTalk Server 2009 provides in-depth coverage of all aspects of mapping to enable you to quickly and efficiently incorporate logic that will fulfill your mapping requirements. While the mapping techniques will be useful for all versions of BizTalk Server, the code is tailored toward BizTalk Server 2006 R3 and demonstrates the latest approaches to standard maps, electronic data interchange, and RFID components. You'll refer again and again to the multiple solutions that will help solve your new mapping challenges, and soon find this is an essential reference for any BizTalk implementation.